Document on China's policy towards Latin America and the Caribbean - República Popular China, Gobierno de la (2014)
As an important part of the group of developing countries, Latin America and the Caribbean constitute a relevant force in the current international scenario. The new circumstances bring renewed development opportunities for Sino-Latin American and non-Caribbean relations. The purpose of the Chinese Government's elaboration of the Policy Paper for Latin America and the Caribbean is to express more clearly the objectives of the Chinese policy towards the region, to set forth the guiding principles of cooperation in the various areas during a given period. of the future and to promote the continuous healthy, stable and integral development of Sino-Latin American and Sino-Caribbean relations.